1990
DOI: 10.1111/j.1095-8649.1990.tb05928.x
|View full text |Cite
|
Sign up to set email alerts
|

A new method for karyological studies in teleost fishes

Abstract: A simple method employing CoCI, is described which has application in the rapid preparation of fish chromosomes for research and teaching. The benefits of this method include low initial skill level, relatively inexpensive equipment and supplies, and the production of a high number of metaphase spreads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…Chromosome preparations were obtained from the anterior kidney cells after in vivo treatment with colchicine (Bertollo et al, 1978). Some specimens were previously treated with yeast suspension (Lee and Elder, 1980), or cobalt chloride solution (Cucchi and Baruffaldi, 1990) for mitotic stimulation. In addition to conventional Giemsa staining, the chromosomes were analyzed after Mithramycin (Schmid, 1980) and Distamycin/…”
Section: Citogenética Evolutiva Do Grupo Hoplias Lacerdae Um Comportmentioning
confidence: 99%
“…Chromosome preparations were obtained from the anterior kidney cells after in vivo treatment with colchicine (Bertollo et al, 1978). Some specimens were previously treated with yeast suspension (Lee and Elder, 1980), or cobalt chloride solution (Cucchi and Baruffaldi, 1990) for mitotic stimulation. In addition to conventional Giemsa staining, the chromosomes were analyzed after Mithramycin (Schmid, 1980) and Distamycin/…”
Section: Citogenética Evolutiva Do Grupo Hoplias Lacerdae Um Comportmentioning
confidence: 99%
“…Topical treatment with cobalt chloride solution demonstrated that this compound is a potent inducer of metaphase in larvae and pupae of Melipona. Cucchi and Baruffaldi (1990) recommended an injection of 500 mL 65 mM cobalt chloride solution per 100 g body weight in fish. We opted for topical application, and the quantity that produced the best results in bees was 4 mL 65 mM cobalt chloride solution per individual.…”
Section: Resultsmentioning
confidence: 99%
“…The technique described for fish by Cucchi and Baruffaldi (1990) was adapted to bees. We applied 4.0 mL 65 mM cobalt chloride solution topically in the dorsal region of defecating larvae and pupae [white-eyed pupa (Pw), pink-eyed pupa (Pp), brown-eyed pupa (Pb), brown-eyed pupa with light pigmented body (Pbl), black-eyed pupa with pigmented body (Pbd)] of M. scutellaris.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of mitotic stimulation in vertebrates relies on the immunological response to antigens, which can be obtained from a wide variety of sources: live microorganisms such as yeasts (Lee and Elder, 1980;Lozano et al, 1988); biological compounds such as horse serum (Ojima and Kurishita, 1980) and phytohemagglutinin, a lectin found in plants able to induce mitosis (Baruffaldi et al, 1992;Takai and Ojima, 1995); natural or induced infection with parasites such as Ichthiophirium multifilis (Moreira-Filho and Bertollo, 1991) and parasitic mollusk larvae (Woznicki et al, 2004), and chemical agents such as phenylhydrazine (Cucchi and Baruffaldi, 1989) and cobalt chloride (Cucchi and Baruffaldi, 1990;Woznicki et al 2004). All these methods trigger, to different degrees, the proliferation of defense cells, which is macroscopically characterized by an enlarged kidney, the hematopoietic organ in fish (Kunz, 2004).…”
Section: Introductionmentioning
confidence: 99%